Industrial Imperialism and the Museum: A Coal Biography - Anaïs Walsdorf (Museum & Society)
In the nineteenth century, coal was an invaluable resource that served as the foundation and power of British imperialism. This object biography traces the journey of a piece of coal from its primeval formation in Aoteroa New Zealand to its current home in Britain’s national science collection. As it travelled through Wellington’s Colonial Museum, the Vienna International Exhibition of 1873, the British metallurgist John Percy’s Collection, and finally the Science Museum Group’s collections, the rock took on different meanings and values. Examining the specimen’s biography provides a perspective on industrial imperialism that centres museums as technologies of empire and extraction within the context of climate crisis and ongoing Indigenous struggles for land and sovereignty.